On the points of strong summabiity of the Fourier series - Gabisoniya , O. D. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The points of a function f ∈ L at which there are given estimates of the rate of convergence to zero of the strong arithmetic means of its Fourier series and the trigonometrically conjugate series are characterized.